Challenges for using organizational climate tools for measuring teacher job satisfaction - Yahya Don; Mohd Faiz Mohd Yaakob; Wan Rozimi WanHanafi; Mat Rahimi Yusof; Muhamad Dzahir Kasa; Mohd Sofian Omar-Fauzee; Hareesol Khun In-Keeree (Institute of Advanced Engineering and Science, 2021)
The organizational environment includes not only the landscape of a school, but also the components of school learning resources, student relations, communication-collaboration, decision-making and instructional innovation. According to the ministry of education, many schools do not have the new facilities needed for successful teaching and learning to meet the potential needs of the workforce. Further investigation is still needed as to how these elements make teachers enjoy a working environment, particularly in Kedah, Malaysia. It would also help the State department of education to address unresolved school issues. The aimed of this research is to examine primary school teachers' understanding of their teacher satisfaction and organizational environment. The design of this study was mix-method consisting of a survey (quantitative approach) and a semi-structured interview (qualitative approach). A sample of 220 teachers in 23 primary schools in Alor Janggus, Kedah participated in this study. On the other hand, a total of 20 teachers were interviewed to identify factors that would lead to teacher satisfaction at work and an organizational environment. The content analysis was used to identify the themes that emerged from the semi-structure interview. The themes emerged from the semi-structure interviews are student relationships, decision-making, school infrastructure, teamwork and educational creativity. Suggestions for future research are discussed in more detail.